LIQUIDITY-PROFITABILITY TRADEOFF EXISTENCE IN TURKEY: AN EMPIRICAL INVESTIGATION UNDER STRUCTURAL EQUATION MODELING - Baser, Furkan; Gokten, Soner; Kucukkocaoglu, Guray; Ture, Hasan (Copernican Journal of Finance & Accounting, 2017)
Firms in emerging markets could show a tendency to have high liquidity positions by ignoring the liquidity-profitability tradeoff in terms of working capital management due to gained experiences from stressed times. Accordingly, this study empirically examines the validity of liquidity-profitability tradeoff in Turkish market via structural equation modeling. The functions of liquidity and profitability as latent variables of the model are constituted from Piotroski’s criterias of liquidity/solvency, operating efficiency and profitability. The hypothesized model for the inexistence of the validity of liquidity-profitability tradeoff was verified and there is a moderate level of positive effect between liquidity and profitability in Turkey. The findings indicate that (1) current ratio or its variants as single-handed variables are inadequate to explain liquidity- profitability relation and (2) leverage seems to be the most important indicator as taken into account on working capital management decisions. Turkish firms apply prudent working capital management to overcome possible liquidity shocks.